A compreensão da experiência do adoecer pela perspectiva de pessoas com câncer hospitalizadas: um olhar fenomenológico existencial - Silva, Aline Agustinho da (2015)
Being a phenomenon that permeates the existence, sickening becomes an important target of reflections for different approaches. As a human experience, it holds a scientific character, but primarily singular from anon-reductive posture regarding the conception of pathos. Conceiving human appropriation with regard to one s own ways of selfcommunication and communication with the world, it s possible to observe different means of action by hospitalized patients who deal with sickening by cancer. While some don't succeed in giving any meaning to the living of this phenomenon, others glance sickening as a growing horizon in their life journey. Based on the knowledge that so many other ways of being in the world can be present among these people, this study states as its main objective to search for comprehension of the sickening experience by the perspective of cancer patients under hospitalization. To research the internment experience in oncology infirmary and to comprehend the unveiling of senses in the experience of sickening by cancer constitute the specific objectives. Aiming to conciliate the proposal of this research with the practical knowledge acquired by the researcher as a hospital psychologist, the tools used for the research were the narrative interview and the field diary. The data was collected in a large hospital in the city of Recife - PE, in an oncology infirmary, with participants of both sexes and with the minimum age of 18. The theoretical fundamentals were based upon the studies of the psychiatrist Viktor Frankl, the data were analyzed by the perspective of the philosopher Dulce Critelli regarding the unveiling of senses and of Gadamer concerning his notion of conversation and fusion of horizons. The results were obtained as narratives that allowed the development of a new look in the sickening phenomenon, demystifying some culturally established beliefs that restrict the experience of cancer to intense and inevitable suffering.